2019
DOI: 10.4103/psychiatry.indianjpsychiatry_412_18
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and daytime sleepiness among professionals in India: A web-based survey

Abstract: Background: The likelihood of the relation between Internet overuse and comorbid psychiatric conditions is on the rise. However, sleep disturbances are common psychiatric symptoms associated with internet overuse. Our objective was to examine the association of Internet overuse with excessive daytime sleepiness, sleep problems in professionals from India. Materials and Methods: This was a web-based cross-sectional study through a predesigned questionnaire which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Table 2 summarizes sociodemographic characteristics of interest and measures of COVID-19 related worry score, sleep (insomnia and daytime sleepiness), and severity of depressive symptoms. 53.45% and 19.69% of the participants reported low to severe levels of insomnia (i.e., ISI ≥8) and daytime sleepiness (i.e., ESS ≥11), respectively (levels notably higher than those reported in typical samples not exposed to severe situational stress; 18.6% & 14% respectively [ 41 , 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes sociodemographic characteristics of interest and measures of COVID-19 related worry score, sleep (insomnia and daytime sleepiness), and severity of depressive symptoms. 53.45% and 19.69% of the participants reported low to severe levels of insomnia (i.e., ISI ≥8) and daytime sleepiness (i.e., ESS ≥11), respectively (levels notably higher than those reported in typical samples not exposed to severe situational stress; 18.6% & 14% respectively [ 41 , 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Sleep patterns further influenced health outcomes, with 228 students (68.9%) having regular sleep patterns, attributed to good dietary habits and early academic schedules. However, 103 students (31.1%) had irregular sleep patterns due to homesickness, financial issues, academic stress, and frequent nighttime mobile use, aligning with an Indian study that found social media addiction contributed to irregular sleep (25). Socioeconomic status played a crucial role, with the majority of students from a middle socioeconomic background (185, 55.9%) having normal BMI.…”
Section: Discussionmentioning
confidence: 64%
“…Elevated BMI has been linked to increased levels of Internet addiction according to several studies (13)(14)(15). Additionally, sleep issues such trouble falling asleep or waking up early have also been linked to this addiction (16). According to a Chinese study (17), Internet addiction is strongly linked to poor sleep quality.…”
mentioning
confidence: 99%